(untitled) (Castilla. Estudios de Literatura, 2016)
This paper is based on a theorical-critical emptiness constatation, al least apparent, in the literary reflection of XVIth and XVIIth that is necessary to analyze for the best knowledge of our study’s object: the satire in the new Balladry. The following study consists of three phases: first, the theorical-critical delimitation of satire in the literary thought at XVIth and XVIIth centuries; secondly, the relation of satire expressive-referential model with the genre structural-strofic of new Balladry; finally, the study of satirical procedure in a representative baldad of Pedro Liñán de Riaza.